Fungsi Tari Balanse Madam dalam Kehidupan Sosial Masyarakat Nias Bandar Raya Padang: (The Functions of the Balanse Madam Dance in the Social Life of Nias Society in Padang City) - Indrayuda (Wacana Seni Journal of Arts Discourse, 2009)
The Balanse Madam dance is a type of traditional dance of the Nias people who have been living in Padang city since a long time ago. The Balanse Madam dance is often performed during social occasions of the Nias people such as weddings, births of newborn babies, and thanksgiving ceremonies. As a traditional heritage of Nias society, Balanse Madam dance functions as a medium for social interaction, integration and entertainment. Consequently, the Balanse Madam dance is connected to various ceremonial customs which are coducted by the Nias people in Padang City.